2011
DOI: 10.5251/ajsir.2011.2.1.69.77
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of heavy metals (Cu, Pb, Ni) pollutants and the vulnerability of groundwater resource in Okrika of Rivers State, Nigeria

Abstract: The chemical mobility of heavy metal pollutants (Cu, Pb, and Ni) is fundamental to the understanding of their environmental accessibility, toxicity and geochemical behaviour to be able to account for the safety and vulnerability of the groundwater resource in the study area. In this work, EDXRF spectrometer was used to determine the total concentration of the metals in the samples and the concentrations left in the residual fractions after extraction. FAAS was used for the chemical analysis of the test sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…However, nickel concentration during the wet season was largely due to the residual fraction (78.0%) ( Figures 1&2). Findings from this study agreed with Tamunobereton-ari et al, 27 that reported nickel in the residual fraction within the range of 65-85%. Similarly, Iwegbue et al, 26 observed that nickel was prevalent in the residual and organic matter bound fractions which are relatively immobile.…”
Section: Nickelsupporting
confidence: 92%
See 1 more Smart Citation
“…However, nickel concentration during the wet season was largely due to the residual fraction (78.0%) ( Figures 1&2). Findings from this study agreed with Tamunobereton-ari et al, 27 that reported nickel in the residual fraction within the range of 65-85%. Similarly, Iwegbue et al, 26 observed that nickel was prevalent in the residual and organic matter bound fractions which are relatively immobile.…”
Section: Nickelsupporting
confidence: 92%
“…Osakwe et al, 24 had reported lead to be mostly found in the residual fraction of Imo River. Tamunobereton-ari et al, 27 had earlier reported lead to be about 60-80% in the residual fraction of Okrika river sediment. However, Horsfall et al, 28 had reported lead to appear in the first fractionexchangeable (52.90%) for Okrika river sediment.…”
Section: Leadmentioning
confidence: 94%
“…The mixture was shaken in the extraction tube for 6 hours at room temperature using a mechanical shaker. The mixture was centrifuged at 3000rpm for 10minutes and the supernatant immediately was used for analysis or stored at 40°C prior to analysis with Micro Plasma Spectroscopy [13,14].…”
Section: Speciation Studies Of the Soil /Sediment Samplesmentioning
confidence: 99%
“…Oil spill incidence is caused by several factors including vandalism and rupture of pipeline (Aigberua et al, 2017). About 95% of the population of the Okrika people who live along the Okrika River and its estuaries solely depend on groundwater for their domestic uses since their surface water sources are severely polluted by the direct discharge of domestic and industrial effluents and wastes into them (Tamunobereton-ari et al, 2011). Therefore, the presence and concentration of heavy metals in water bodies may be influenced by human activities even as sediments serve as the final sink of heavy metals in the water body (Asimiea and Lawal, 2017).…”
mentioning
confidence: 99%